2003
DOI: 10.1002/elan.200390031
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Kinetics of Ferrocene at Microcrystalline Boron‐Doped Diamond Electrodes: Effect of Solvent and Electrolyte

Abstract: Cyclic voltammetric measurements were made using well-characterized microcrystalline boron-doped diamond thinfilm electrodes to test the material×s responsiveness for ferrocene as a function of scan rate, solvent, and electrolyte composition. Apparent heterogeneous electron transfer rate constants, k8 app , of 0.042 AE 0.015, 0.048 AE 0.015, and 0.008 AE 0.002 cm/s were observed in 0.1 M NaClO 4 /CH 3 CN, 0.1 M TBAClO 4 /CH 3 CN, and 0.1M TBAClO 4 /CH 2 Cl 2 , respectively. These rate constants, obtained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(19 reference statements)
3
15
1
Order By: Relevance
“…Noel and co-workers 77 reported that the rate constants on platinum, glassy carbon and polypropylene composite graphite (CPP) electrodes in ferrocene-TBAP-CH 3 CN solution were 5.1 Â 10 À3 , 4.5 Â 10 À3 and 3.3 Â 10 À3 cm s À1 , respectively which are of a similar value to those observed with the SWCNTs directly attached to silicon. In contrast to this, Swain and co-workers 78 reported rate constants on microcrystalline boron-doped diamond (BDD) and glassy carbon electrodes in ferrocene-TBAP-CH 3 CN solution were 4.8 Â 10 À2 and 5.1 Â 10 À2 cm s À1 , respectively, which are about 10 times larger than those observed in this work. The exact reason for the difference using glassy carbon reported by Swain and Noel (a 10 fold difference) could be due to different experimental conditions such as the treatment of electrode surfaces and the purity of the solvent/electrolyte.…”
Section: Electrochemistrycontrasting
confidence: 93%
“…Noel and co-workers 77 reported that the rate constants on platinum, glassy carbon and polypropylene composite graphite (CPP) electrodes in ferrocene-TBAP-CH 3 CN solution were 5.1 Â 10 À3 , 4.5 Â 10 À3 and 3.3 Â 10 À3 cm s À1 , respectively which are of a similar value to those observed with the SWCNTs directly attached to silicon. In contrast to this, Swain and co-workers 78 reported rate constants on microcrystalline boron-doped diamond (BDD) and glassy carbon electrodes in ferrocene-TBAP-CH 3 CN solution were 4.8 Â 10 À2 and 5.1 Â 10 À2 cm s À1 , respectively, which are about 10 times larger than those observed in this work. The exact reason for the difference using glassy carbon reported by Swain and Noel (a 10 fold difference) could be due to different experimental conditions such as the treatment of electrode surfaces and the purity of the solvent/electrolyte.…”
Section: Electrochemistrycontrasting
confidence: 93%
“…Quantitatively, it has been observed that in acidic and neutral media, 2-2.5-fold higher i pa values are obtained on the GC than the BDD and surprisingly, the increase is five fold in the alkaline media. Similar results were also obtained by Compton et al on the anodic oxidation of bromide [21] and reduction of chlorine [22]. The above results once again reflect the earlier observation on the merits of the GC.…”
Section: Studies On the Anodic Peak Potential And Currentsupporting
confidence: 92%
“…They have also demonstrated that during the electrochemical oxidation of halides [20] and the reduction of chlorine gas [21], different electrodes such as edge plane pyrographite (EPPG), basal plane pyrographite (BPPG) and the GC shows supremacy over the BDD. Moreover, an earlier investigation has clearly indicated that the charge transfer kinetics on the GC and BDD electrodes in aprotic solvents for ferrocene/ferrocenium redox couple are almost similar [22]. The present work is an attempt to explore a close look on these issues.…”
Section: Introductionmentioning
confidence: 92%
“…A possible way of 'greening' electroanalytical techniques is in the introduction of novel electrode materials avoiding the use of mercury which is unattractive due to its inherent toxicity [2,3]; bare glassy carbon, modified carbon paste, and boron-doped diamond electrodes are fast becoming the choice for much electroanalysis [4,5,6]. In addition these electrode materials are highly suitable for use in conjugation with ultrasound, which is, for example, applied during the accumulation step in anodic stripping voltammetry resulting in greatly increased sensitivity of the technique with a reduction in deposition times [7,8].…”
Section: Introductionmentioning
confidence: 99%